2021
DOI: 10.1186/s12889-021-12392-2
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and tooth loss: the Brazilian National Health Survey, 2019

Abstract: Background Little is known about the presence of two or more chronic conditions (multimorbidity) on tooth loss between adults and older adults. Understanding the mechanisms of multimorbidity on tooth loss is essential to inform policy development. This study aims to investigate the association between multimorbidity and severity of tooth loss in Brazilian adults and older adults. Methods We analysed data from a nationally representative sample of 8… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
0
7
1
Order By: Relevance
“…Using a process mining technique, Larvin et al (2021) suggested that tooth loss might contribute to the developmental trajectories of multimorbid diseases. However, to the best of our knowledge, only one study has examined the association between multimorbidity and tooth loss in a large-scale population study; using data from the Brazilian national health survey, Bomfim et al (2021) reported older adults (≥60 years) with multimorbidity were 17% more likely to lose functional dentition (i.e., lost more than 23 teeth or be edentulous) compared to those without multimorbidity. Notably, the association was even stronger among young adults (18-59 years); those with multimorbidity were 32% more likely to lose functional dentition than their counterparts with one or no chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Using a process mining technique, Larvin et al (2021) suggested that tooth loss might contribute to the developmental trajectories of multimorbid diseases. However, to the best of our knowledge, only one study has examined the association between multimorbidity and tooth loss in a large-scale population study; using data from the Brazilian national health survey, Bomfim et al (2021) reported older adults (≥60 years) with multimorbidity were 17% more likely to lose functional dentition (i.e., lost more than 23 teeth or be edentulous) compared to those without multimorbidity. Notably, the association was even stronger among young adults (18-59 years); those with multimorbidity were 32% more likely to lose functional dentition than their counterparts with one or no chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the high DMFT figures in 35/44-year-old Brazilians and Filipinos (15.8, 12.9 respectively) are on par with the high number of missing teeth in seniors (20.5, 17 respectively). Severe tooth loss defined by <10 remaining teeth occurs in almost half of 60-79-year-old Brazilians, 54 indicating the somewhat low effectiveness of the comparatively advanced Brazilian dental system. However, what is hard to explain is the huge difference among Indonesian citizens, with a low DMFT in adults aged 35/44 (4.5) followed by a high MT value in seniors of 16.3 (Table 3) later in life.…”
Section: Resultsmentioning
confidence: 99%
“…This leads us to infer that any difference between groups regarding inflammatory and NETosis biomarkers, if detected, would not be attributed to intraoral sources. It is possible to state that the study participants had an oral health condition similar to the Brazilian elderly population [ 53 , 54 ]. Furthermore, there was no difference in salivary flow rates between the groups.…”
Section: Discussionmentioning
confidence: 99%